Epistemologi Fikih Siyâsah - Masykuri Abdillah (AHKAM : Jurnal Ilmu Syariah, 2012)
Abstract: Epistemology of Fiqh Siyâsah. Islam is not merely a theological system but also a social and state system. The ulamas through their ijtihad formulated Islamic teachings on state in ‘ilm al-siyâsah al-Islâmiyyah or fiqh siyâsah (Islamic political knowledge). This is defined as “knowledge that deals with managing Islamic state affairs in terms of systems and laws that are in line with the Islamic principles, even if there is no certain argumentation (from the Quran and the Sunnah)”. This knowledge has grown dynamically, because it can interact with political ideas and systems from the outside as well as local culture, including with the modern political system.Keywords:  fiqh siyâsah, siyâsah syar‘iyyah, islamic political thought, islamic political system, the theory of Islamic politicAbstrak: Epistemologi Fikih Siyâsah. Islam tidak hanya mencakup sistem kepercayaan dan ibadah, tetapi juga sistem kemasyarakatan dan kenegaraan. Para ulama dengan ijtihad mereka merumuskan ajaran-ajaran Islam tentang negara ini dalam ‘ilm al-siyâsah al-Islâmiyyah atau fikih siyâsah (ilmu politik Islam). ‘Ilm al-siyâsah ini didefiniskan sebagai “ilmu yang membahas tentang pengaturan urusan-urusan negara Islam dalam hal sistem dan undang-undang yang sejalan dengan dasar-dasar Islam meskipun dalam pengaturan ini tidak ada dalil tertentu (dari Alquran maupun Hadis)”. Ilmu ini berkembang dengan dinamis karena ia bisa berinteraksi dengan gagasan dan sistem politik dari luar serta budaya lokal, termasuk dengan sistem politik modern.Kata Kunci: fikih siyâsah, siyâsah syar‘iyyah, pemikiran politik Islam, sistem politik Islam, teori politik IslamDOI: 10.15408/ajis.v12i1.977